(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article is devoted to alternative methods of dispute resolution in the Republic of Uzbekistan. The author examines the use of alternative methods of dispute resolution in Uzbekistan and their features. The author also studied the current legislation of the Republic of Uzbekistan on mediation and its current state, indicated the problems associated with the application of the mediation procedure and developed ways to solve them.